An analysis of the monetary policy transmissio mechanism and the real economy in Nigeria - Central Bank of Nigeria, Research Department; Research Department, Central Bank of Ngeria (Abuja. Central Bank of Nigeria, 2013)
The study examines empirically the Central Bank of Nigeria's monetary policy transmission mechanism and the ral economy in Nigeria
Includes bibliographical references.
oif 30/06/17
Ref.
Keywords: Monetary policy; Banks and banking, Central; Nigeria